Topiramate for acute affective episodes in bipolar disorder. - Vasudev, K; Macritchie, K; Geddes, J; Watson, S; Young, A (2006)
BACKGROUND: Bipolar disorder is a common recurrent illness with high levels of chronicity. Treatment resistance persists despite the use of established medications, such as lithium and valproate. New medications are required for the treatment of refractory cases. Retrospective and open-label trials have suggested that the anticonvulsant topiramate may be efficacious in bipolar disorder. There is a need to clarify the evidence available in the form of randomised controlled trials for its use in bipolar disorder. OBJECTIVES: To review the evidence for the efficacy and acceptability of topiramate in the treatment of acute mood episodes in bipolar disorder. SEARCH STRATEGY: The Cochrane Collaboration Depression, Anxiety and Neurosis (CCDAN) group search strategy was used. The following databases were searched:The Cochrane Collaboration Depression, Anxiety and Neurosis Controlled Trials Register (CCDANCTR), September 2003;The Cochrane Controlled Clinical Trials Register (CCCTR), September 2003;EMBASE (1980 to December 2003);MEDLINE (1966 to December 2003);LILACS;PsycLIT;Psyndex.Reference lists of relevant papers and major textbooks of mood disorder. Handsearches (specialist journals and conference proceedings). Authors, other experts in the field and pharmaceutical companies were contacted for knowledge of suitable published or unpublished trials. SELECTION CRITERIA: Randomised controlled trials which compared topiramate with placebo or with active agents in the treatment of any acute mood episodes in bipolar disorder. Participants were patients with bipolar disorder and were males and females of all ages. DATA COLLECTION AND ANALYSIS: Data extraction and methodological quality assessment were performed independently by two reviewers. For analysis, relative risk was used for binary efficacy outcomes and the weighted mean difference or standardised mean difference was used for continuously distributed outcomes. MAIN RESULTS: One randomised controlled trial met the inclusion criteria for the review, a comparison between topiramate and bupropion sustained release (SR) in the adjunctive treatment of depressed patients with bipolar disorder. However, the trial had several limitations in methodology and in the description of data. Its data regarding efficacy required clarification before it could be analysed according to the protocol of this systematic review. From the limited data available, topiramate had efficacy similar to bupropion SR in the adjunctive treatment of bipolar depression. Both groups of subjects suffered a high drop-out rate. There was no significant difference between the topiramate and the bupropion treated groups in those dropping out for any reason (relative risk 1.60, 95% confidence interval 0.65 to 3.96). There was no significant difference in those withdrawing from the study due to adverse effects (relative risk 1.50, 95% confidence interval 0.51 to 4.43). Although the data on weight loss were not analysed formally, weight loss was marked in the topiramate treated group. Several unpublished trials have been identified and data from these trials may be included in future reviews. AUTHORS' CONCLUSIONS: There is insufficient evidence on which to base any recommendations regarding the use of topiramate in any phase of bipolar illness, either in monotherapy or as an adjunctive treatment.